2021
DOI: 10.2478/jtes-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Challenges of Teleworking Employees of Educational Institutions in Latvia During COVID-19

Abstract: This study reflects motivation as one of the most important resources for achieving the goals of sustainable education. Motivation is a challenge as well as an important goal for the sustainability of education. The impact of COVID-19 has reached such proportions that the professional life of educators may never be the same again. Some of the key questions to consider in the context of educational sustainability: What are the most effective tools for motivating educators? What are the most important mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…They were best valued among teleworkers, while they were the worst valued by non-teleworkers. This result ties in with the findings of the study of Rozentale et al (2021) who pointed these organizational measures are one of the most important motivation tools by employees as the different sectors in Latvia, during the lockdown, and with the research carried out by the International Labor Organization [International Labor Organization (ILO), 2020] according to which:…”
Section: Discussionsupporting
confidence: 75%
“…They were best valued among teleworkers, while they were the worst valued by non-teleworkers. This result ties in with the findings of the study of Rozentale et al (2021) who pointed these organizational measures are one of the most important motivation tools by employees as the different sectors in Latvia, during the lockdown, and with the research carried out by the International Labor Organization [International Labor Organization (ILO), 2020] according to which:…”
Section: Discussionsupporting
confidence: 75%
“…The study concluded with the statement that future education with institutional support would be needed (Goller & Rieckman, 2022). Other study pointed out that during the COVID-19 pandemic motivation as a tool for career development and education was around only 50 % in the education sector (Rozentale et al, 2021).…”
Section: Bibliometric Analysis Of Teacher Education For Sustainabilitymentioning
confidence: 99%
“…The future of the sustainable development depends on how we perceive the concept (Kahriman-Ozturk et al, 2012;Hopkins & McKeown, 2002). The major challenge lies in its practice, which requires ethical, moral, attitudinal and behavioral changes and awareness of motivation particularly under uncertainty conditions (Steinemann, 2003;Rozentale et al, 2021;SalÓte et al, 2021). In this regard, education plays a vital role in changing these aspects, including the reorientation of education for sustainable development (Selby, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The online educational platforms have been used increasingly during COVID-19. The pandemic completely changed the stakeholdersí attitudes towards online learning (Rozentale et al, 2021). Both students and parents were obliged to accept the online educational systems and platforms to sustain education irrespective of their own preferences and regardless of their digital literacy.…”
Section: Education For Sustainabilitymentioning
confidence: 99%